How marketing mix (7Ps) affect the patients’ selection of a hospital: experience of a low-income country - Ravangard, Ramin (J Egypt Public Health Assoc, 2020)
BACKGROUND: Applying marketing mix in the hospitals is necessary for their success. It is also important to optimize the price, developing services, increasing health literacy, and improving financial resources. Experts and patients may have different views about the factors that influence the decision for choosing a hospital. This study was conducted to identify the factors in the marketing mix which influence patients’ selection of hospitals in Shiraz, Iran. METHODS: A cross-sectional study involving patients assigned to six hospitals; three selected private and three corporate public hospitals in Shiraz in southern Iran in 2018 composed the study sample. From the inpatients and outpatients referring to these hospitals, 300 patients were included using a stratified sampling method proportional to size. Their views on the status of the selected hospitals regarding the 7Ps model of the hospital marketing mix (product, people, price, place, promotion, process, and physical environment) were assessed using a 5-point Likert scale. Data were collected by administering a validated researcher-developed questionnaire (CVI = 2.65, α = 0.929). RESULTS: Among 44 components of marketing mix according to 7Ps model, “specialty of health service providers” had the best status (mean (SD) 4.15 ± 0.82) from the patients’ viewpoints. Among the 7Ps, “physical environment” and “people” had better status respectively. In contrast, the studied hospitals had the poorest status in “promotion.” Significant relationship was revealed between the private and corporate public hospitals in terms of price, promotion, and process (P < 0.05). Pearson’s correlation revealed a direct relationship between all the components of marketing mix in the hospitals (P < 0.001). CONCLUSION: The studied hospitals have an appropriate status in physical environment and people mix but poor status in promotion mix. It is therefore necessary for these hospitals to pay more attention to the “promotion mix” irrespective of the related costs. Moreover, as “process mix” had a high significant correlation with the other marketing mix, managers can improve their marketing services through correcting their current processes.